2014
DOI: 10.1161/circinterventions.114.001555
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Switching Between Clopidogrel and Prasugrel Among Patients With Acute Myocardial Infarction Treated With Percutaneous Coronary Intervention

Abstract: Background-Although randomized clinical trials have compared clopidogrel with higher potency ADP receptor inhibitors (ADPris) among patients with myocardial infarction, little is known about the frequency and factors associated with switching between ADPris in clinical practice. Methods and Results-We studied 47 040 patients with myocardial infarction treated with percutaneous coronary intervention, who received either clopidogrel or prasugrel within 24 hours of admission at 361 US hospitals from July 2009 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 25 publications
3
35
2
2
Order By: Relevance
“…6,[8][9][10][11][24][25][26] Nevertheless, there is little evidence until now to justify switching regimens. TROPICALACS is currently the only trial investigating a concept of guided deescalation of P2Y 12 inhibition in an allcomers cohort of patients with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10][11][24][25][26] Nevertheless, there is little evidence until now to justify switching regimens. TROPICALACS is currently the only trial investigating a concept of guided deescalation of P2Y 12 inhibition in an allcomers cohort of patients with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A previous analysis examined switching from clopidogrel to a higher‐potency P2Y 12 inhibitor during the index MI hospitalization; younger age, private health insurance, and presentation with STEMI were associated with intensification of P2Y 12 inhibitor therapy, whereas prior history of atrial fibrillation, stroke, peripheral artery disease, or heart failure were associated with clopidogrel continuation 17. Patients switched to a higher‐potency P2Y 12 inhibitor were more likely to have had a recurrent MI during their index hospitalization than patients continued on clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent ischemic events while receiving clopidogrel therapy may affect physician decision making because of perceived clopidogrel “failure,” although these events may not necessarily reflect inadequate platelet inhibition. In patients with ACS, in‐hospital reinfarction while taking clopidogrel is associated with a higher likelihood of a switch to prasugrel 17. Postdischarge switching is rare, and most switches are from prasugrel or ticagrelor to clopidogrel, driven by cost considerations 18.…”
mentioning
confidence: 99%
“…It was also shown that clopidogrel was effective enough in the carriers of wild-type (*1*1) CYP2C19, which represents a normal metabolism rate of this drug (Reese et al, 2012). In addition, only up to one-fourth of the prasugrel-treated patients are discharged from hospital for antiplatelet treatment at home (Sandhu et al, 2013;Bagai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%